Time dependent changes in protein expression induced by intermittent theta burst stimulation in a cell line - Ismail, Fatima Y.; Krishnan, Manigandan; Jayaraj, Richard L.; Bru-Mercier, Gilles; Pessia, Mauro; Ljubisavljevic, Milos R. (Frontiers in Neurology, 2024)
Intermittent Theta Burst Stimulation (iTBS), a non-invasive brain stimulation technique, is recognized for its ability to modulate cortical neuronal activity. However, its effects over time and the dynamics following stimulation are less well understood. Understanding the temporal dynamics of iTBS effects is essential for optimizing the timing and frequency of stimulation in therapeutic applications. This study investigated the temporal changes in protein expression induced by iTBS in Neuro-2a cells. We analyzed protein expression in retinoic acid-differentiated Neuro-2a cells at multiple time points—0.5, 3, 6, 12, and 24 hours post-iTBS—using Western blot and immunocytochemistry techniques. Our findings reveal a significant early increase in neurotransmitter receptor subunits, neurotrophic factors, and cytoskeletal proteins within the first 0.5 hour following iTBS. Notably, proteins such as mGLuR1, NMDAR1, GABBR2, and β-tubulin III showed substantial increase in expression. However, the effects of iTBS on protein expression was not sustained at later timepoints. These results suggest that iTBS can transiently alter the expression of specific proteins in Neuro-2a cells. Future research should investigate the potential benefits of repeated stimulations within the early time window to refine iTBS interventions, potentially expanding their research and clinical applications.